Evaluation of informal education in higher education - Ćetojević, Helena (Norma, 2023)
Informal education stems from everyday and spontaneous activities related to work, family, or leisure time and is not organized or structured in terms of goals, time, or learning support. Its immediacy, naturalness, and lucidity are its main characteristics, distinguishing it from formal and non-formal education. Due to constant technological and societal changes, there is a necessity to optimize informal education and encourage more flexible educational pathways. The process of validating individual knowledge, skills, and abilities is highly complex and requires support from the entire educational system and society. The aim of this study was to highlight the benefits and significance of competencies acquired through informal learning. Through examples of good practices from foreign universities, questions arose regarding the possibilities of implementing the validation of informal education in Serbian universities. The ultimate focus of the study was on the insufficient affirmation of informal education, systemic and procedural constraints, and suggestions for overcoming them in the near future.